LEGAL PROTECTION FOR CHILD AND FEMALE WORKERS FROM A HUMAN RIGHTS PERSPECTIVE - Apriliani, Kadek; Oka Permadhi, Putu Lantika (Faculty of Law, Universitas Pekalongan, 2024)
The issue on violence and discrimination against child and female workers in Indonesia remains significant to date. The government aims to protect children and women, prevent violence and discrimination, and address these issues through legal instruments and other promotion. This study centers its objective on identifying the factors contributing to human rights violations against child and female workers, as well as promotion to prevent and address these violations. The study employs normative juridical methods and data collection techniques based on journals, articles, laws, and conceptual approaches. The results indicate that poverty, culture, low levels of education, and economic pressure are factors contributing to human rights violations against children. The marginalization of women in the workplace, their subordinate position in society and culture, stereotypes against them, low education, patriarchal culture, and the interests of the authorities are all factors behind human rights violations against female workers. Promotion to prevent such violations include making laws regarding the protection of children and women, among other measures. Keywords: Child and Female Workers, Human Rights, Legal Protection